Effect of suprathermal electrons on the intensity and Doppler frequency of electron plasma lines - Guio, P; Lilensten, J (SPRINGER VERLAG, 1999)
In an incoherent scattering radar experiment, the spectral measurement of the so-called up- and downshifted electron plasma lines provides information about their intensity and their Doppler frequency. These two spectral lines correspond, in the backscatter geometry, to two Langmuir waves travelling towards and away from the radar. In the daytime ionosphere, the presence of a small percentage of photoelectrons produced by the solar EUV of the total electron population can excite or damp these Langmuir waves above the thermal equilibrium, resulting in an enhancement of the intensity of the lines above the thermal level. The presence of photo-electrons also modifies the dielectric response function of the plasma from the Maxwellian and thus influences the Doppler frequency of the plasma lines. In this paper, we present a high time-resolution plasma-line data set collected on the EISCAT VHF radar. The analysed data are compared with a model that includes the effect of a suprathermal electron population calculated by a transport code. By comparing the intensity of the analysed plasma lines data to our model, we show that two sharp peaks in the electron suprathermal distribution in the energy range 20-30 eV causes an increased Landau damping around 24.25 eV and 26.25 eV. We have identified these two sharp peaks as the effect of the photoionisation of N-2 and O by the intense flux of monochromatic HeII radiation of wavelength 30.378 nm (40.812 eV) created in the chromospheric network and coronal holes. Furthermore, we see that what would have been interpreted as a mean Doppler drift velocity for a Maxwellian plasma is actually a shift of the Doppler frequency of the plasma lines due to suprathermal electrons.